Managing Karachi's Water Supply and Sanitation Services : Lessons from a Workshop - World Bank (Washington, DC, 2014)
Water services in Pakistan's major cities and urban centers remain fragmented and intermittent-no city currently has 24 hours of water supply for seven days a week. This impairs the ability of cities to support economic growth and meet basic needs. Faced by this challenge, the Nazim of the City District Government of Karachi (CDGK) suggested in mid-2004 that the Water and Sanitation Program - South Asia (WSP-SA) help to arrange a discussion about lessons for Karachi from Water and Sanitation (W&S) services reform in large cities and urban areas elsewhere in the world. In follow up discussions, it was agreed that although Karachi would be the entry point, the workshop should also include discussion of similar challenges elsewhere in Pakistan. Key W&S stakeholders from major cities in Pakistan, the central government and the provincial government of Sindh (where Karachi is located) attended a two-day workshop in Karachi on February 23-24, 2005. The WSP-SA facilitated participation by several resource persons, including practitioners from Manila, Johannesburg, Phnom Penh and from the national water utility in Uganda. The formal presentations and delegates' inputs all emphasized the institutional-rather than technical- nature of the challenges around water and sanitation in Pakistani cities. This message also came through in a number of keynote addresses. A key lesson learned from the workshop is that there is no single solution or model for water management that can be applied everywhere. However, international and Pakistani city experiences all highlight a number of factors crucial for effective reform in most contexts. These factors include the importance of reliable information; the need for performance benchmarks and monitoring; the issue of keeping policymaking, regulation, and provision separate and therefore ensuring a robust accountability framework; strong political leadership,; having a comprehensive plan; sticking to the principles, while being pragmatic in strategy; managing change processes; proving powerful incentives; and the need to have resources to sustain reform plans and initiatives.